Penerapan Hukum Ketenagakerjaan Terhadap Pekerja/Buruh Yang Mengalami Pemutusan Hubungan Kerja (PHK) Menurut Undang-Undang N0.13 Tahun 2003 Tentang Ketenagakerjaan - Rizki Maulana Efendi; Enjum Jumhana; Rizki Apriansyah; Muhammad Solihin; Rosyd Wardan (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
Termination of Employment (TOE) is the termination of an employment relationship due to a matter that results in the expiration of rights and obligations between workers/laborers and employers regulated in Law No. 13 of 2003 concerning employment and secondary legal materials obtained from employment, internet papers and others. The implementation of termination of employment must be in accordance with Law No. 13 of 2003 concerning employment that termination of employment is carried out in several processes, namely deliberation between employees and the Company, if there is an impasse, the last resort is carried out through the court to decide the case. Therefore, the strength of the implementation of labor law is needed through increased supervision, education for the parties, and optimization of the role of labor dispute resolution institutions.